1983
DOI: 10.1097/00000658-198308000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Three Yearsʼ Experience with Esophageal Stapling Device

Abstract: The authors report their experience with forty patients undergoing resection of middle and lower thirds carcinomas of the esophagus or proximal stomach, with esophagogastric or esophagojejunal anastomosis using an end-to-end anastomosis (EEA) stapler. A fatal anastomotic leak occurred in the first two patients and seven other patients died in the early postoperative period from respiratory and cardiovascular complications. Four other patients developed fibrotic strictures between 6 and 24 months after their op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Being aware of this, we antici pate such a complication and add 6-8 externally rein forcing 3-0 atraumatic polyglycolic acid sutures after fin ishing the stapled anastomosis. Behl et al [20] and Huttunen et al [18] use such sutures especially if the dough nuts are incomplete. The stapler has to be held with the handles upward and removed in the same position while observing the intactness of the doughnuts.…”
Section: Discussionmentioning
confidence: 99%
“…Being aware of this, we antici pate such a complication and add 6-8 externally rein forcing 3-0 atraumatic polyglycolic acid sutures after fin ishing the stapled anastomosis. Behl et al [20] and Huttunen et al [18] use such sutures especially if the dough nuts are incomplete. The stapler has to be held with the handles upward and removed in the same position while observing the intactness of the doughnuts.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to a hand-sewn anastomosis, stapler usage results in a higher incidence of postoperative anastomotic stricture formations [8, 9, 10]. Some authors assigned this to be mainly due to the lack of mucosa-mucosa apposition [8, 9, 10]. This was well demonstrated in a study of sutured and stapled colorectal anastomosis in dogs, the sutured anastomosis showed rapid epithelization, however, stapled anastomosis produced a 2- to 4-mm mucosal gap [11].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that recent advances of the EEA sta pling device reduced the incidence of anastomotic leakage [18,19]. It is considered that the intrathoracic anastomo sis using the EEA stapling device is a safe procedure.…”
Section: Discussionmentioning
confidence: 99%